Alternative Practices to Overcome the Environmental Problems in National Park - Keawnuch, Knokkarn (วารสารวิชาการการท่องเที่ยวไทยนานาชาติ, 2015)
Tourism industry is the major sector in business world today. It is fair to say that tourism is now one of the world’s fastest-growing industries. In 2010, the Middle East and Asia had the massive growth of tourists. Many countries rely heavily on the industry with the hope to boost up their national and local economy. For that reason, they attempt to promote their tourism by developing new tourist destinations that are different from others. However, it is vital for all tourism stakeholders; government sectors, non-government sectors, private sectors also local people to concern about impacts from tourism activities. Many host destinations often neglect the fact that a high number of tourists not only enhance their economy but also induce environmental impacts on those destinations. Since, park tourism has increased in recent years and it is likely to create negative impacts, even on a protected area. Yet, protected areas have immense value in educational, recreational, and ecological terms. In order to tackle the negative impacts appropriately the impacts first have to be understood.